Nogo-A Neutralization Improves Graft Function in a Rat Model of Parkinson’s Disease - Seiler, Stefanie; Di Santo, Stefano; Widmer, Hans Rudolf (Frontiers in Cellular Neuroscience, 2016)
Transplantation of fetal human ventral mesencephalic dopaminergic neurons into the striatum is a promising strategy to compensate for the characteristic dopamine deficit observed in Parkinson’s disease. This therapeutic approach, however, is currently limited by the high number of fetuses needed for transplantation and the poor survival and functional integration of grafted dopaminergic neurons into the host brain. Accumulating evidence indicates that contrasting inhibitory signals endowed in the central nervous system might support neuronal regeneration. Hence, in the present study we aimed at improving survival and integration of grafted cells in the host brain by neutralizing Nogo-A, one of the most potent neurite growth inhibitors in the central nervous system. For that purpose, ventral mesencephalic tissue cultures were transplanted into rats with a partial 6-hydroxydopamine lesion causing a hemi-Parkinson’s disease model and concomitantly treated for two weeks with intra-ventricular infusion of neutralizing anti-Nogo-A antibodies. Motor behavior using the cylinder test was assessed prior to and after transplantation as functional outcome. At the end of the experimental period the number of dopaminergic fibers growing into the host brain, the number of surviving dopaminergic neurons in the grafts as well as graft size was examined. We found that anti-Nogo-A antibody infusion significantly improved the asymmetrical forelimb use observed after lesions as compared to controls. Importantly, a significantly three-fold higher dopaminergic fiber outgrowth from the transplants was detected in the Nogo-A antibody treated group as compared to controls. Furthermore, Nogo-A neutralization showed a tendency for increased survival of dopaminergic neurons (by two fold) in the grafts. No significant differences were observed for graft volume and the number of dopaminergic neurons co-expressing G-protein-coupled inward rectifier potassium channel subunit 2 between groups. In sum, our findings support the view that neutralization of Nogo-A in the host brain may offer a novel and therapeutically meaningful intervention for cell transplantation approaches in Parkinson’s disease.